Technology Adaptation: The Case of a Computer-Supported Inter-Organizational Virtual Team1 - Majchrzak, Ann; Rice, Ronald E.; Malhotra, Arvind; King, Nelson; Ba, Sulin (MIS Quarterly, 2000)
The adaptation process for new technology is not yet well understood. This study analyzes how an inter-organizational virtual team, tasked with creating a highly innovative product over a 10 month period, adapted the use of a collaborative technology and successfully achieved its challenging objectives. The study of such a virtual team is especially useful for extending our understanding of the adaptation process as virtual teams have more malleable structures than typical organizational units and controlled group experiments. Data were obtained from observations of weekly virtual meetings, electronic log files, interviews, and weekly questionnaires administered to team members. We found that the team initially experienced significant misalignments among the pre-existing organizational environment, group, and technology structures. To resolve these misalignments, the team modified the organizational environment and group structures, leaving the technology structure intact. However, as the team proceeded, a series of events unfolded that caused the team to reevaluate and further modify its structures. This final set of modifications involved reverting back to the pre-existing organizational environment, while new technology and group structures emerged as different from both the pre-existing and the initial ones. A new model of the adaptation process—one that integrates these findings and those of several previous models—is proposed.